If it's not what You are looking for type in the equation solver your own equation and let us solve it.
20=11k-13
We move all terms to the left:
20-(11k-13)=0
We get rid of parentheses
-11k+13+20=0
We add all the numbers together, and all the variables
-11k+33=0
We move all terms containing k to the left, all other terms to the right
-11k=-33
k=-33/-11
k=+3
| –3(c+2)=–9 | | 10^x=6.14 | | 5x–3(x+4)=16 | | s/3− 2=1 | | 12x+4=4(x+2+2x) | | 12j-7j=15 | | 9p-6p=12 | | 9h-5h=4 | | 3j−10=–1 | | p/4+ 17=19 | | 18-6×+12=-10(9x-4) | | -24=x-2-4 | | 8x+21=21+8x | | 21/4w=62/4 | | −2|x−3|+8=−4 | | 52x-9=97 | | 6+5n=8n–9 | | x^2×4x×15=0 | | 12=9=3a | | 2.5+0.05a=6-0.7a | | y/7+4=11 | | r+45-1=24 | | 3^(7x-6)=8^(5x-8) | | 28/15=x/20 | | 2^x=5.14 | | k2+12k+28=-7 | | 5w+36+w=180 | | 2x-6=-3x-9 | | 1-5x+7=27 | | -10(d+1)=-10 | | 130=(17x+3) | | 20+10x=8x+72 |